THE BEHAVIOR OF MOTHER KEEPING SANITATION IN FOOD ITH THE INCIDENT DIARRHEA ON THE TODDLER IN THE VILLAGE PANEMON SUBDISTRICT SUGIHWARAS THE COUNTY BOJONEGORO - Sulmiati, Endang; Kusyani, Asri; Ningrum, Umi Azizah Kusuma (WELL BEING, 2016)
The incident diarrhea currently mortality is still high, especially on the toddler. One factor cause diarrhea is the behavior of the mother keeping sanitation in food that are less good where the way of treatment or the presentation on will make the food contaminated bacteria and bacteria that if entry into the alimentary canal toddlers will cause diarrhea. The purpose of this research is knowing the behavior of the mother keeping sanitation in food with the incident diarrhea on the toddler. The study design used is analytics correlational the case control. The population of the mother ho have infants in the village Panemon is 145 people, engineering sampling simple random sampling and found samples as much 36 people. Collecting data using questionnaires, the analysis use of the test statistic Rank Spearman with a= 0,05 The result of the study found most of the respondents behave negative and the incident diarrhea 22 respondents (61%). Based on the test statistics there is a behavior mother keeping sanitation in food with the incident diarrhea on the toddler with p value = 0, 000 (p < a = 0,05) and rho = 1,000. Should mother searching for information and learn to change the behavior of the positive keeping sanitation in food that can prevent diarrhea on the toddler. Key words : behavior, diarrhea, mother, toddler.